Community and identity in Castilian histories of the fifteenth century - Kern, Darcy (Sharq al-Andalus, 2021)
La historia fue tan importante para la construcción de la identidad comunitaria y la legitimidad política en el siglo XV como lo es hoy, y en los reinos de España igualmente tenso. Los cronistas y biógrafos católicos castellanos parecen inseguros del estado preciso de los moros en Iberia. Todos estaban de acuerdo con el control político o el señorío de los cristianos castellanos, pero pocos tenían una idea clara de las implicaciones de ese señorío para los moros. ¿Debería permitirse a los moros permanecer como parte de la comunidad una vez que un monarca cristiano castellano tomara el control de su ciudad, región o reino, o no había posibilidad de que pertenecieran? Rodrigo Sánchez de Arévalo (1404-1470), Fernán Pérez de Guzmán (c. 1377-c. 1460), Alonso Fernández de Palencia (1423-1492), Hernando de Pulgar (1436-c. 1492), y Mosén Diego de Valera (1412-1488) dieron diferentes respuestas. Todos coincidieron en que la comunidad castellano-leonesa existía antes de al-Andalus y, por lo tanto, era la comunidad política legítima de Hispania. La mayoría de ellos aceptaron la presencia de Granada de facto pero no de jure. Sin embargo, Arévalo, Valera y Pulgar sugieren la posibilidad de una comunidad política musulmana de jure bajo dominio castellano; Palencia y Guzmán no.
Keywords: dept.his

Book Review: The keepers of the seas the blue age gregg easterbrook PublicAffairs, 2021. 304 pp. - Smith, Jason W. (Science (New York, N.Y.), 2021)
Keywords: article; book.review; dept.his

Understanding the role of wrongdoing in technological disasters: Utilizing ecofeminist philosophy to examine commemoration. - Roe, Sarah M.; Zavar, Elyse (Studies in history and philosophy of science, 2021)
Stemming from human accident, error, or neglect, technological disasters, such as chemical spills, toxic waste contamination, nuclear radiation, transportation accidents, and factory explosions, are products of the modern industrial complex. Toxic contamination of the land can permanently displace people from their homes and erase places from the landscape. Commemoration provides an opportunity to remember the past and celebrate culturally significant place attachments while contributing to the recovery process by aiding in community healing after devastating events. We focus on two key components regarding commemoration after technological disaster, namely the acknowledgement of wrongdoing and the celebration of a resilient population and landscape. We argue that a combination of ecofeminist philosophy and environmental justice frameworks allows for a better understanding of the cycle of disaster and mitigation as it pertains to targeted groups, and that commemorative acts and artifacts following human-made disasters often fail to successfully reform this cycle. Moreover, the combination of ecofeminist philosophy and environmental justice allows us to examine the complex relationship between responsibility and targeted groups through disaster commemoration, which serves as an important way to communicate wrongdoing to both the local and greater population. Through engagement with ecofeminist philosophy and environmental justice frameworks, we explicate how commemoration after technological disaster can disrupt or reinforce systematic inequalities. © 2021 Elsevier Ltd
Keywords: article; artifact; contamination; dept.his; disaster; explosion; factory; human; justice; neglect; peer-reviewed; philosophy; responsibility; toxic waste

Notes on the state of Virginia: an annotated edition - Jefferson, Thomas; Forbes, Robert Pierce (Yale University Press, 2021)
Keywords: Description and travel; Early works to 1800; Early works to 1800; Virginia; History; Virginia; dept.his; faculty_collection